Application of green iron nanoparticles supported on biochar for the removal of selected organochlorine pesticides from water / Samavia Batool - Samavia , Batool (2019)
In this work, novel green iron nanoparticles supported on biochar (INPs-Bg) were prepared for the efficient removal of organochlorine pesticides (OCPs) from water system. For this purpose, four biochars were prepared from four biomass wastes of Rambutan fruit peel (BRtP), Oil palm leaf (BOpL), Jackfruit peel (BJfP) and Sugar cane leaf (BScL). Both green and conventional (chemical) methods were applied for the synthesis of biochar supported iron nanoparticles. Four types of green synthesized biochar supported iron nanoparticles (INPs-BRtP, INPs-BOpL, INPs-BJfP and INPs -BScL collectively named as INPs-Bg) were developed using four extracts of the four biomass wastes named as Rambutan fruit peel (ERtP), Oil palm leaf (EOpL), Jackfruit peel (EJfP) and Sugar cane leaf (EScL), respectively. These extracts act as a green reducing mediator to reduce ferrous oxide (Fe(II)) to zerovalent iron (Fe0), while chemical synthesized biochar supported iron nanoparticles (INPs-BChe) were developed using sodium borohydride as a reducing agent. All samples of nanocomposites (INPs-BChe and INPs-Bg) were characterized by field emission scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), BET surface area and X-ray diffraction (XRD). All samples of nanocomposites were applied for the removal of highly toxic six selected organochlorine pesticides (OCPs) named as p,p’-dichloro-diphenyl-trichloroethane (p,p’-DDT), o,p’- dichloro-diphenyl trichloroethane (o,p’-DDT), endosulfan I, aldrin, heptachlore and hexachlorobenzene from aqueous solution and oil palm plantation drainage (OPPD) water samples. Variable parameters including pH, dosage of adsorbent, initial concentration of adsorbate and time were studied. The equilibrium data of isotherm adsorption for OCPs on all nanocomposites were fitted well to Langmuir isotherm. The kinetic isotherms were fitted first to Pseudo-second order adsorption model and then to Pseudo-first order reduction rate model for all types of nanocomposites. The removal percentage, adsorption capacity (mg/g) and reaction rate constant (